Groundwater dynamics and recharge assessment in an unconfined aeolian sand aquifer - Bécher Quinodóz, Fátima Noelia (2016)
In the sandy plain of the South of Córdoba province, Argentina) the unconfined aquifer is used mainly for agricultural activities. The objective of this work is to show the estimation of the recharge (R) rate in the unconfined aquifer, using the water table fluctuation method (WTF). Furthermore, considerations in relation to monthly recharge and discharge (D) rhythms were performed. The studied unconfined aquifer consists mainly of sandy aeolian sediments with values of hydraulic conductivity in the order of 1.5 m/d. The water table is slightly undulating and hydraulic gradients and flow velocities are low, controlled by lithology and the regional plain topography. The relationship between groundwater and surface water bodies is variable, but in general, the aquifer provides water to the river and to the lagoons. The parabolic dunes of this sandy plain environment show a typical behavior of preferential recharge areas. That is, an important and quick answer of water table to the arrival of precipitations and then the discharge to the base level, the neighboring lagoon in the parabolic dune. Using monthly estimation, an annual average recharge value of 12% of total precipitation was obtained. When the relationship between P and R was analyzed, the 91 % of recharge episodes were clearly dependent on the rainfall behavior. Winter shows very low recharge but a great effectiveness because the recharge arrives to the aquifer from delayed wetting fronts, although almost there were not rainfalls. Nevertheless, the major amount of recharge has occurred in the end of spring, summer, and early autumn. The ratio R/D for the whole series was positive which means that the aquifer recharge predominated, a fact that is coherent with the higher position of the water table at the end of the studied series. These results assure the existence of annual water replacement to the aquifer, a very important feature for a region that depends on groundwater resources.